2023
DOI: 10.3390/toxics11040311
|View full text |Cite
|
Sign up to set email alerts
|

Special Issue on “Insights on Ecotoxicological Effects of Anthropogenic Contaminants in Aquatic Organisms”

Abstract: In human history, many key points have characterized technological progress, such as the use of metals, which began in prehistoric times and continues to the present day, with many industrial uses [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It was suggested that Zn and Cu had greater toxicity to acidogens as compared with Pb. Other reports [23] showed inhibition to acidogens caused by Cu and Zn at a concentration of 1-10 mg dm -3 and 5-40 mg dm -3 , respectively [23,24]. It was suggested that metals may inhibit the conversion of VFA to methane during anaerobic digestion [25].…”
Section: Discussionmentioning
confidence: 95%
“…It was suggested that Zn and Cu had greater toxicity to acidogens as compared with Pb. Other reports [23] showed inhibition to acidogens caused by Cu and Zn at a concentration of 1-10 mg dm -3 and 5-40 mg dm -3 , respectively [23,24]. It was suggested that metals may inhibit the conversion of VFA to methane during anaerobic digestion [25].…”
Section: Discussionmentioning
confidence: 95%